Quantitative rheo-microscopy of soft matter - Villa, Stefano; Edera, Paolo; Brizioli, Matteo; Trappe, Veronique; Giavazzi, Fabio; Cerbino, Roberto (Frontiers in Physics, 2022)
Direct observation of the microscopic material structure and dynamics during rheological shear tests is the goal of rheo-microscopy experiments. Microscopically, they shed light on the many mechanisms and processes that determine the mechanical properties at the macroscopic scale. Moreover, they permit for the determination of the actual deformation field, which is particularly relevant to assess shear banding or wall slip. While microscopic observation of the sample during mechanical probing is achieved by a variety of custom and commercial instruments, the possibility of performing quantitative rheology is not commonly available. Here, we describe a flexible rheo-microscopy setup that is built around a parallel-sliding-plate, stress-controlled shear cell, optimized to be mounted horizontally on a commercial microscope. Mechanically, soft materials with moduli ranging from few tens of Pa up to tens of kPa can be subjected to a variety of waveforms, ranging from standard step stress and oscillatory stress to more peculiar signals, such as triangular waves or {any other signal of interest}. Optically, the shear cell is designed to be compatible with different imaging methods (e.g. bright field or confocal microscopy). Most of the components of the shear cell are commercially available, and those that are not can be reproduced by a standard machine shop, easing the implementation of the rheo-microscopy setup in interested laboratories.